Smart contracts and decentralized finance as novel tools in EU market stability: An integrated panel data and qualitative analysis - SPAHO, Mateo; BELERAJ, Iris (Edelweiss Applied Science and Technology, 2025)
This paper investigates the dual impact of Decentralized Finance (DeFi) and smart contracts on European Union (EU) market stability, with a focus on the role of regulation. The research problem centers on understanding how the rapid growth of DeFi interacts with emerging regulatory frameworks to shape financial stability. The purpose is to provide an integrated analysis that combines quantitative data with qualitative legal insights to inform policy. The methodology employs a fixed-effects panel data model to analyze the effect of DeFi market capitalization, smart contract deployments, and transaction volumes on a market stability index across EU member states, while also incorporating a qualitative review of the EU’s regulatory landscape, including the Markets in Crypto-Assets (MiCA) Regulation [1]. Key findings indicate that while DeFi’s growth correlates with increased market volatility, regulatory interventions like MiCA appear to have a stabilizing effect. The paper concludes that a clear and harmonized regulatory framework is crucial for mitigating the risks associated with DeFi while fostering responsible innovation. The relevance of this study lies in its timely contribution to the ongoing policy debate on DeFi regulation and its implications for financial stability in the EU [2].